HAKIKAT MAKNA FITNAH LEBIH KEJAM DARI PEMBUNUHAN PERSPEKTIF PENAFSIRAN WAHBAH AZ-ZUHAILI - Sholeh, Moh. Jufriyadi; Firdaus, Hendri Happy (Institut Dirosat Islamiyah Al-Amien Prenduan, 2024)
One important topic in the Quran is fitnah, which has serious consequences, especially when it comes to someone's reputation. This emphasizes the importance of a proper understanding of the nature of fitnah, especially in the modern era. Although murder is considered a more serious crime in the legal realm, the detrimental effects of fitnah cannot be ignored. This research attempts to uncover the essence of fitnah, often considered trivial compared to murder, based on the perspective of Wahbah al-Zu?ayl? in his interpretation. Misunderstandings when interpreting Quranic verses highlight the importance of historical context, interpretation, and understanding of religious terminology. Referring to exegetes and scholars can help better understand the Quran. Thus, this research aims to delve deeper into Allah's message through the Quran, especially in dealing with fitnah, which is often considered trivial but has profound impacts. Further with the focus of this research, it will at least address two objectives: first, to understand Sheikh Wahbah al-Zuhayli's perspective that fitnah is more severe than murder, and second, to explain the relevance of fitnah being considered more severe than murder to current phenomena, with the hope that society can correctly understand the message conveyed by the researcher. This research uses a literature research method, utilizing sources such as the Quran, hadiths, interpretations, books, journals, and manuscripts related to Quranic verses about fitnah. Sheikh Wahbah Zuhayli's interpretation that fitnah is more severe than murder has strong relevance in the contemporary context. Fitnah, according to his perspective, involves physical threats or torture but encompasses various forms such as social pressure, conflicting ideologies, or worldly temptations. The relevance of this interpretation is evident in the modern context, where fitnah can manifest in various forms such as social pressure, ideological conflicts, and temptations of worldly life. Careful understanding of Quranic verses, along with an understanding of historical context and religious terminology, is a crucial key in facing the challenges of fitnah.